STRATEGI DIPLOMASI PERTAHANAN NEGARA DALAM TEKS ARTHASHASTRA - AYU NIKKI AVALOKITESVARI (Veda Jyotih: Jurnal Agama dan Sains, 2023)
National defense is a very important aspect in maintaining the existence and sovereignty of a country. Since ancient times Chanakya in his very famous treatise Arthasastra emphasized the importance of diplomacy and efforts to build the strength of a country. This paper aims to examine the text of Arthasastra as the basis for the Defense Diplomacy strategy. Indonesia adopted a Sanskrit slogan in the military world which indicated the close relationship between Indonesia’s defense and the rich heritage of Asian civilization with the influence of Indian texts. Chanakya emphasized that the state must build defenses, be ready to go to war but be able to maintain peace. A country is seen as having to be authoritative so that other countries, either with hostile tendencies or as partners, will have high respect. However, Arthasastra emphasized that the highest goal of a country is to build prosperity with defense and security as a prerequisite for building prosperity for a country.